Analisis Sistem Informasi Berbasis Cobit 5 (Studi Kasus : LTC UKSW) - NOVIAN STEVEN FARERA MESSAKH; Andeka Rocky Tanaamah (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
The application of IT in a company is a framework that can increase organizational profits. IT must be properly managed to generate targeted benefits. LTC is an organization that uses Cobit 5 as a tool to manage business objectives related to existing IT governance. Governance requires analysis to evaluate, assess maturity and make recommendations. LTC has not evaluated existing IT governance, so LTC does not have a framework to be able to find out the conditions, benefits and impacts of implementing IT that has been implemented. Cobit 5 is a comprehensive overall framework, because it can be adapted to existing governance in LTC. The domain on Cobit 5 the author is focused on is